2022
DOI: 10.1080/02103702.2022.2086770
|View full text |Cite
|
Sign up to set email alerts
|

The key role of community inLearning by Observing and Pitching Into family and community endeavours (El papel clave de la comunidad enAprender por medio de Observar y Acomedirseen las actividades de la familia y la comunidad)

Abstract: This article focuses on communities' contributions to a way of learning that seems to be common in many Indigenous communities of the Americas and among people with heritage in such communities: Learning by Observing and Pitching In to family and community endeavours (LOPI). We briefly contrast this with community contributions in Assembly-Line Instruction, a way of learning that is common in Western schooling, to highlight the distinct contributions of community in these two ways of learning. We theoretically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 88 publications
0
23
0
11
Order By: Relevance
“…If previous empirical work has not identified the role of grandparents in the development of grandchild prosociality, why would this be different in the case of Latinx families? Fitting in with theories of prosociality in Latinx families (Carlo & Conejo, 2019;Rogoff & Mejía-Arauz, 2022), theories in cultural anthropology and evolutionary biology have suggested that living conditions that include extended family members may enhance early sociocognitive, emotional, and physical development (Hawkes, 2020;Hawkes et al, 1997;Hrdy, 2009;Hrdy & Burkart, 2022).…”
Section: Grandparents Grandchildren and Latinx Culturementioning
confidence: 98%
“…If previous empirical work has not identified the role of grandparents in the development of grandchild prosociality, why would this be different in the case of Latinx families? Fitting in with theories of prosociality in Latinx families (Carlo & Conejo, 2019;Rogoff & Mejía-Arauz, 2022), theories in cultural anthropology and evolutionary biology have suggested that living conditions that include extended family members may enhance early sociocognitive, emotional, and physical development (Hawkes, 2020;Hawkes et al, 1997;Hrdy, 2009;Hrdy & Burkart, 2022).…”
Section: Grandparents Grandchildren and Latinx Culturementioning
confidence: 98%
“…Her book The Cultural Nature of Development (2003) introduced a cultural perspective on development to many students and colleagues. Most recently, she and her students have focused on "Learning by Observing and Pitching In" (LOPI) to family and community endeavors (Rogoff & Mejía-Arauz, 2022), and Rogoff continues to draw on the Guatemalan experience as a touchstone for her thinking (Rogoff et al, 2011). Some of Kagan's students have contributed more directly to the continuing concern with culture as a creator of children's environments for society and polity to manage, particularly in the preschool years.…”
Section: The Legacymentioning
confidence: 99%
“…For Rogoff, the experience of living and working in a village on Lake Atitlán proved formative for a career investigating what young children learn from their cultural surround, and how they “learn to learn.” Her book The Cultural Nature of Development (2003) introduced a cultural perspective on development to many students and colleagues. Most recently, she and her students have focused on “Learning by Observing and Pitching In” (LOPI) to family and community endeavors (Rogoff & Mejía-Arauz, 2022), and Rogoff continues to draw on the Guatemalan experience as a touchstone for her thinking (Rogoff et al, 2011).…”
Section: The Legacymentioning
confidence: 99%
“…LOPI is a way of organizing learning opportunities in which children are broadly integrated in the activities of their families and communities and learn by attentively contributing to the endeavors around them, in a multifaceted process. (Rogoff, 2014, p. 69) LOPI is represented by a prism with seven facets dealing with: the community organization of learning; motive; the social organization of endeavours; the goal of learning; the means of learning; communication; and assessment (see Rogoff & Mejía-Arauz, 2022). The prism represents 'a coherent system' in which each facet interrelates with and is reflected in the others (Rogoff, 2014, p. 75).…”
Section: Perspectives and Theoretical Frameworkmentioning
confidence: 99%
“…Where all of the participants are speakers of the language, the revitalization strategy calls for incorporating non-speakers into those situations and supporting intentional Indigenous language immersion. However, instead of immersion 'classes' or 'lessons' in households and community spaces, in a LOPI-based approach to language revitalization, communication in family and community endeavours is carried out 'by mutually building on the shared context of events' (Rogoff & Mejía-Arauz, 2022; Figure 1). The endeavours may be of any kind where LOPI ordinarily occurs, such as gardening, preparing and eating meals, sewing, beadwork, recreational games, household and community chores, traditional rituals and ceremonies, subsistence activities, home-improvement projects, shopping and similar activities, such as those described in other studies of informal learning (see Rogoff et al, 2016, for an overview).…”
Section: A Lopi-based Approach To Indigenous Language Revitalizationmentioning
confidence: 99%